2001
DOI: 10.1021/ic000911+
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Magnets:  Jahn−Teller Isomerism and the Origin of Two Magnetization Relaxation Processes in Mn12 Complexes

Abstract: Several single-molecule magnets with the composition [Mn12O12(O2CR)16(H2O)x] (x = 3 or 4) exhibit two out-of-phase ac magnetic susceptibility signals, one in the 4-7 K region and the other in the 2-3 K region. New Mn12 complexes were prepared and structurally characterized, and the origin of the two magnetization relaxation processes was systematically examined. Different crystallographic forms of a Mn12 complex with a given R substituent exist where the two forms have different compositions of solvent molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 60 publications
6
115
0
5
Order By: Relevance
“…Thus, the highest-frequency line is assigned to the ͉12, Ϯ 12͘ → ͉12, Ϯ 11͘ transition, and so on. The lines are much narrower ͑11 eV FWHM͒ than those observed for other SMMs, e.g., 23 eV FWHM for Mn 12 Ac. The fit procedure showed that the lines are inhomogeneously broadened and best described by Gaussian line shapes.…”
Section: B Mn 6 (2) U Eff é 53 K Vs Mn 6 (3) U Eff é 864 Kmentioning
confidence: 64%
“…Thus, the highest-frequency line is assigned to the ͉12, Ϯ 12͘ → ͉12, Ϯ 11͘ transition, and so on. The lines are much narrower ͑11 eV FWHM͒ than those observed for other SMMs, e.g., 23 eV FWHM for Mn 12 Ac. The fit procedure showed that the lines are inhomogeneously broadened and best described by Gaussian line shapes.…”
Section: B Mn 6 (2) U Eff é 53 K Vs Mn 6 (3) U Eff é 864 Kmentioning
confidence: 64%
“…The prefactor τ 0 = 70 s obtained from the Arrhenius analysis of the relaxation dynamics at H z = 0 is unusually large, 7 − 11 orders of magnitude larger than in Mn 12 [1][2][3][4] and other SMMs [5,6,[8][9][10][11][12][13]. It is much larger than the timescale of ac magnetic susceptibility measurements, which are usually used to characterize and quantify the relaxation behavior in SMMs.…”
Section: Analysis and Discussionmentioning
confidence: 91%
“…Chemists have joined forces with physicists in an attempt to fully characterize and understand the new phenomena and to develop strategies to design and prepare other members of this new family of single molecule magnets (SMMs). So far a number of further SMMs have been discovered, mostly by means of ac susceptibility, among them several manganese clusters, [8][9][10][11] as well as tetranuclear vanadium [12] and iron [13] complexes. All these compounds contain clusters with at least four paramagnetic centers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spacing between the QMT steps associated with the FR species (~0.4 T) is not all that dissimilar to those of the SR species (~0.45 T), suggesting that they possess similar uniaxial anisotropy constants D. [14][15][16] Subsequently, detailed synthetic work by Christou, Hendrickson and co-workers, involving ligand substitution and crystallization from a variety of solvents, resulted in the discovery of many different forms of Mn 12 possessing essentially the same neutral Mn 12 O 12 core. 11,12,[17][18][19][20][21][22][23][24][25][26][27] However, important differences have been inferred from X-ray and magnetic studies. Most notably, the various Mn 12 complexes can be grouped broadly into two categories, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases where the FR species are obtained in single-crystal form, X-ray studies show that one or more of the Jahn-Teller (JT) elongation axes associated with the Mn III atoms are abnormally oriented 18,19,21,24,25,33 in comparison to the usual SR form of Mn 12 . 26,27,[34][35][36][37] This is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%